2000
DOI: 10.1053/rapm.2000.6450
|View full text |Cite
|
Sign up to set email alerts
|

The bilateral effect of stellate ganglion block on the facial skin blood flow

Abstract: Our study suggests that stellate ganglion block may increase the contralateral regional skin blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…4,5 Facial skin blood flow was bilaterally increased after SGB. 6 In addition, celiac artery blood flow, which is not innervated by the cervical sympathetic fibers, was increased after SGB. 7 It is assumed that there should be a region where tissue blood flow decreases to balance with increased blood flow on the block side after SGB because circulating blood volume is constant.…”
Section: Discussionmentioning
confidence: 92%
“…4,5 Facial skin blood flow was bilaterally increased after SGB. 6 In addition, celiac artery blood flow, which is not innervated by the cervical sympathetic fibers, was increased after SGB. 7 It is assumed that there should be a region where tissue blood flow decreases to balance with increased blood flow on the block side after SGB because circulating blood volume is constant.…”
Section: Discussionmentioning
confidence: 92%
“…It is believed that inhibition of the ciliospinal center of Budge results in an excitatory sympathetic response leading to ipsilateral pupillary dilation, facial hyperhidrosis, and lid lift, and therefore a paradoxical contralateral Horner’s syndrome 11. Previous literature showed that increased hand warming and facial skin blood flow occurred bilaterally in about 50% of cases after unilateral SGB 12,13. These findings suggest that bilateral sympathetic blockade occurs commonly to a degree to produce these functional changes, but not enough to produce gross anatomic changes, including Horner’s syndrome.…”
Section: Discussionmentioning
confidence: 80%
“…SGB is widely considered to be an effective therapeutic modality for various diseases, such as complex regional pain syndrome (CRPS) of the upper limb, pain in the face or head, and so on [12,13]. Also, some authors have reported that SGB has an effect on anosmia and hyposmia [7,8].…”
Section: Discussionmentioning
confidence: 99%